Assessment of the soil fertility status of lands under upland farming practices at Sabal Sarawak, Malaysia - Ho, Soo Ying (Universiti Malaysia Sarawak(UNIMAS), 2015)
Rapidly changing land uses at the upland areas due to the need of subsistence and monetary income have resulted in the intensification of upland agriculture. Incorporation of various agrochemicals on a permanent cultivation land could be detrimental to the tropical environment especially on the naturally fragile upland soils. Various efforts are progressing towards sustaining the soil resources at the upland areas. However, very limited information are available on the current soil fertility and nutrient status under intensified form of agricultural practices via cash crops cultivation at the upland areas of Sarawak. In this study, assessment on the soil nutrient status under various perennial cash crops farming by smallholder farmers at upland area of Sabal was conducted. The soil fertility in these farmlands was determined using soil indices, notably Soil Evaluation Factor (SEF). In addition, the study also clarified the influence of current land management practices on soil nutrient stocks under cash crops cultivation. This study was conducted at Sabal, Sarawak where majority of the communities are smallholder farmers and presently conduct various forms of cash crop farming. Soil samples were collected at the depth of 0-10 cm and 30-40 cm from various land uses namely: secondary forest, rubber, Hevea brasiliensis; oil palm, Elaeis guineensis and pepper, Piper nigrum farmlands for soil physicochemical analysis. Additional soil samples were also collected from the fertilizing points at 0-10 cm depth of oil palm stands and pepper vines. Soil profile descriptions were conducted at the representative study sites to collect the baseline data of the soils at the study area. Interview with the farmland owners were also conducted to obtain information on family background, land use history and cultural practices. The results showed that there were different types of land management practices for the cash crop farming in the study area. In general, only small amount of fertilizers were applied in young rubber farmlands as compared to oil palm and pepper farmlands. On average, approximately 0.2 t ha-1 to 6.8 t ha-1 of compound N-P-K fertilizers were applied annually at oil palm and pepper farmlands. With regard to the different land uses, the soils at the study area were acidic in nature, characterized by sandy texture with low exchangeable bases (K, Mg and Ca). The clay contents and soil Total C were low thus, corresponds to low soil CEC level at the study area. Various land uses were further divided into young secondary forest (Y-SF), old secondary forest (O-SF), before tap rubber farmland (BT-R), after tap rubber farmland (AT-R), before harvest oil palm farmland (BH-OP), after harvest oil palm farmland (AH-OP), before harvest pepper farmland (BH-P) and after harvest pepper farmland (AH-P). In terms of soil physicochemical properties, among different land uses, rubber farmlands resembled to those in secondary forest. Meanwhile, accumulation of nutrient contents, notably soil available P as the effect of fertilizers application was observed in oil palm and pepper farmlands. In addition, soils at both oil palm and pepper farmlands showed high soil bulk density and soil hardness, indicating considerable soil compaction due to regular farm work and maintenance. At the surface soils (0-10 cm), the BH-P farmlands showed the greatest SEF value which was 9.58, followed by Y-SF (9.09), BT-R farmlands (9.04), AH-OP farmlands (8.98), O-SF (6.84), BH-OP farmlands (6.79) and least for AT-R farmlands (6.62). In terms of soil nutrient stocks under various crops cultivation, the soil nutrient stock under AT-R farmlands were low and similar to those in O-SF. Conversely, soil nutrient stocks in AH-OP farmlands and AH-P farmlands were higher as compared to O-SF, as fertilizers were added into the soils regularly for crops production. As farmers were able to produce satisfactory latex yield, current rubber farming with minimal input of fertilizers and soil disturbances can be regarded as sustainable at the uplands of Sabal. However, the intensified oil palm and pepper cultivation should be reconsidered as it involves significant use of agrochemicals, particularly oil palm cultivation which occupied a larger farmlands area. Knowledge on agrochemicals, especially on fertilizers application along with crop nutrient requirements should be enhanced among the farmers to ensure the effective use of agrochemicals. Furthermore, appropriate and strategic land use planning as well as techniques of good agricultural practice (GAP) should be incorporated and adapted by the local farmers in conserving soil fertility towards sustainable upland agriculture in the future.